Proposed Business Strategy for JRC in Indonesia Coffee Industry - Andrani, Renitta; Aditya Wibowo, Satya (The Indonesian Journal of Business Administration, 2017)
Abstract – Coffee is an important beverage for most of society around the world. Not only for consumers’ delight of drinking it, but also for its economic value for the coffee beans producing and exporting countries, such as Indonesia. However, local consumption of coffee beans in Indonesia is still low, compared to another coffee importers countries. Another issue of Indonesia is illegal logging, which related on preservations of its rainforests. JRC is a coffee specialty producer and roaster in Jakarta, which try to convince and stop illegal logging in the fragile eco-systems yet still generate income for local people by introducing intercropping method, on growing coffee in the forests. The increasing growth of Indonesian middle class society resulted of lifestyle changes in the society, and cause the increasing of coffee consumption by local consumers. Based on these opportunities, JRC trying to increase its target sales, but the changed in the number of sales are not significant. The purpose of this final project is to create business strategy in order to increase target sales of JRC in Jakarta area. Research methodology of this final project using both quantitative and qualitative approach. For quantitative method, approach is taken by handing questionnaire to the respondents. Meanwhile, qualitative data is done through interview with credible subject matter experts from the company. Conceptual framework of the final project using both internal and external analysis. In internal analysis, will be conducted using STP analysis (Segmentation, Targeting, and Positioning), Marketing Mix using 4P’s (Product, Place, Pricing, and Promotion), Value Chain analysis and analyzing primary data from interview. While external analysis use PESTEL analysis (Political, Economic, Social, Technological, Legal and Environmental), Porter’s 5 Forces, analyzing primary data from questionnaire distribution and analyzing competitor. The results of both external and internal analysis will be used to evaluate in SWOT Analysis (Strength, Weakness, Opportunity and Threat). Strategy formulating for business solution will be conducted using TOWS matrix that related to all factors in SWOT analysis. The purpose of strategy formulation is to find business solution that can be generate and implement in marketing strategy and to propose recommendation to JRC. Keywords: Coffee Industry, Business Strategy, Marketing Strategy